Exploring the Role of the Mixed Methods Approach in Facilitating an Improved Understanding of Food Access in Masiphumelele - Mbambo, Thandeka (Department of Environmental and Geographical Science, 2023)
This thesis focuses on the food environment of Masiphumelele and seeks to understand how mixed-method approaches could be employed to facilitate an advanced understanding of food access in Masiphumelele. Masiphumelele was chosen as the case study for this research project as this work is sponsored by the IDRC-funded Nourishing Spaces project, which works in Masiphumelele. Based on the food-environment framework, this thesis embarked on the valuation of food environment literature to establish the interconnections between the four pillars of food security, food environments, and food systems in the urban context. The findings of this study endorse other work on food environments that issues of access should not only be understood through the physical and socioeconomic lens but also consider related social aspects that shape, enable or constrain food choices and behaviours in urban contexts. The findings of this thesis underscore the need for the reconceptualization of food environments beyond the simplistic physical and economic access framings which dominate earlier food environment work characterized by food deserts. Following the assessment of existing literature on food security, the discourse revealed that adopting the mixed-method approach that integrates participatory and retail mapping is an applicable conceptual framework for exposing socio-spatial dynamics influencing food utilization and food accessibility in the urban context. Building on the growing scholarly and policy interest of mixed methods approaches this thesis endeavours to establish the significance of the mixed-method approach in facilitating an improved understanding of food access in Masiphumelele.